A preliminary analysis of the wear pathways of sliding contacts on temporomandibular joint total joint replacement prostheses - Pinto-Borges, Henrique (2021)
In the last years, several materials and design have been assessed in an attempt to improve the mechanical performance of temporomandibular joint total joint replacement (TMJ TJR) prostheses. However, the wear of the TMJ TJR condyle to the polymer-based fossa component during loading and sliding movements. That promotes the release of debris and risks of toxicity to the surrounding tissues. The purpose of this study was to perform a narrative literature review on the wear of TMJ TJR sliding contacts and potential toxicity of metallic debris to the patients. Previous studies reported a significant deterioration of the sliding contact surfaces of TMJ TJR prostheses. Material loss as a result of wear can cause a TMJ TJR condyle/fossa mismatch and the modification of the contact pressure and chewing loading. As a further consequence of wear, metal particles are released to the surrounding tissues with a high risk of local tissue and systemic toxicity through the bloodstream. The presence of particles induces the stimulation of inflammatory reactions depending on the concentration and size of debris. Thus, CoCr-based condyle release metallic ions and sub-micron particles that can be engulfed by macrophages or internalized by other tissue cells. The wear and material loss of TMJ TJR could be decreased by design optimization and novel materials with low friction and contact pressure. That consequently decrease the amount of metallic ions and particles to the surrounding tissues, preventing peri-prosthetic inflammatory reactions.